Pengaruh Model Pembelajaran Pendidikan Matematika Realistik Indonesia (PMRI) Terhadap Kemampuan Numerasi Siswa - Wijayanti, Amelia Anggun; Marhaeni, Nafida Hetty (Cartesian: Jurnal Pendidikan Matematika, 2024)
The aim of this research is to determine the influence of the Indonesian Realistic Mathematics Education (IRME) learning model. The subjects of this research were 10th grade students at a public high school in Yogyakarta. This type of research uses experimental research with a quasi-experimental or quasi-experimental design. The data collection technique uses a distribution of pretest and posttest questions. The research instrument used was a test sheet. The data analysis used was the normality test, homogeneity test, and paired sample t-test. The results of the research show that there is a difference in the average score between the pretest and posttest which shows that there is a significant increase in the average of 33.30. The hypothesis results show a comparison of the tcount and ttable tests, where the tcount value is 26.281 and the ttable value is 2.030. This means that the value of tcount > ttable. This means that the Indonesian Realistic Mathematics Education (IRME) learning model influences students' numeracy abilities.